The Structural Simplification Hypothesis and the Premodifiers in Nigerian English - Mayowa Akinlotan (Anglica. An International Journal of English Studies)
This paper conducts a corpus-based study of the occurrence/non-occurrence, structural pattern, and forms of the premodifier in the Nigerian English noun phrase, comparing the scenarios that emerge with those of the British and Ghanaian varieties of English. These three phenomena, which are crucial to the nature of premodifier in new varieties of English, are investigated in relation to predictors representing syntactic function, register, post-dependent syntactic weight, and animacy, showing, among other things, the extent to which structural complexity/simplicity is present in the structure of the premodifiers studied. Corpus findings indicate that premodifiers are more likely to occur (53%) than not (47%) and that simple premodifiers (i.e. one-word premodifier structural pattern (79%)) are signifi cantly preferred to complex premodifiers (i.e. two-word at 17% and longer patterns at 4%). Relating to form, single premodifiers are most likely to be realized as adjectives. It is also found that the alternation between simple and complex premodifiers is most strongly predicted by the syntactic functions that the NP performs, as well as the syntactic weight present in the post dependent slot. Register, which is reputed as a very strong indicator of structural variation (Schils and De Haan 1993; Biber et al. 2007; Schilk and Schaub 2016) is outweighed by syntactic function and post-dependent weight.